Utilisation of maternal health services in Ethiopia: a key informant research project. Issue 2 (17th February 2016) - King, Rosemary; Jackson, Ruth; Dietsch, Elaine; Hailemariam, Assefa
ABSTRACT: This article explores the application of key informant research to examine barriers and facilitators to maternal health services in rural and pastoralist Ethiopia. The key informants were health extension workers (HEWs) who assist women with birth preparedness and facilitate timely referral to health centres for birth. While women encounter many barriers to giving birth in health facilities, where HEWs are supported by their communities and health centre staff, they can effectively encourage women to travel to health centres to give birth with skilled birth attendants rather than at home with unskilled relatives or traditional birth attendants.